Assessment of alkaline treatment of palm kernel fiber and curing duration on selected properties of cement-paper composite boards. Issue 1 (1st January 2021) - Akinwande, Abayomi Adewale; Adediran, Adeolu Adesoji; Balogun, Oluwatosin Abiodun; Adesina, Olanrewaju Seun; Olasoju, Oluseyi Samuel; Owa, Adebayo Felix; Erinle, Tunji John; Akinlabi, Esther Titilayo
Abstract: In a bid to develop a cheaper alternative material for particleboard, fiber/particulate reinforced cement-paper composites were produced. The paper-cement matrix had 12 wt. % of cement and the matrix was reinforced with 10 wt. % fixed amount of coconut shell powder and varied amount of palm kernel fiber (0, 0.5, 1.0, 1.5, 2.0, and 2.5 wt. %). Two separate groups of samples were produced; one containing untreated fiber (UPKF), in varied proportions of 0–2.5 wt. % and the second containing alkaline-treated fiber (TPKF), in varied proportion of 0–2.5 wt. % fiber. Samples produced were cured for 28 and 49 days and examined for physical, mechanical, and thermal properties as well as microstructural features. The result obtained revealed improvement in properties of samples as fiber proportion increased. Comparison of the properties obtained indicates that alkaline-treated samples gave a better performance than the untreated counterparts, which was reflected in the sum of property ratio for each mix. The value for TPKF samples was higher than the value for UPKF samples. Also, samples cured for 49 days had better performance than the ones cured for 28 days for both UPKF and TPKF. Evaluation of the three experimental variables, fiber addition, alkaline treatment, and curing length proved that curing was more effective in enhancing the properties of the composites developed, especially the mechanical properties.